Urban mobility design - Coxon, Selby; Napper, Robbie; Richardson, Mark (Elsevier, 2019)
Focusing from the perspective of the user, Urban Mobility Design investigates how designed mobility and design processes can respond to and drive the emerging social and technological disruptions in the passenger transport sector. Profound technological advances are changing the mobility expectations of city populations around the world. Transportation design is an under represented research area of urban transportation planning. Urban Mobility Design addresses this gap, providing research-based analysis on current and future needs of urban transportation passengers. The book examines mobility from a uniquely multidisciplinary perspective, involving a variety of innovative design and transportation planning approaches.